Spatial Genome Organization: From Development to Disease - Sivakumar, Aishwarya; de las Heras, Jose I.; Schirmer, Eric C. (Frontiers in Cell and Developmental Biology, 2019)
Every living organism, from bacteria to humans, contains DNA encoding anything from a few hundred genes in intracellular parasites such as Mycoplasma, up to several tens of thousands in many higher organisms. The first observations indicating that the nucleus had some kind of organization were made over a hundred years ago. Understanding of its significance is both limited and aided by the development of techniques, in particular electron microscopy, fluorescence in situ hybridization, DamID and most recently HiC. As our knowledge about genome organization grows, it becomes apparent that the mechanisms are conserved in evolution, even if the individual players may vary. These mechanisms involve DNA binding proteins such as histones, and a number of architectural proteins, some of which are very conserved, with some others having diversified and multiplied, acquiring specific regulatory functions. In this review we will look at the principles of genome organization in a hierarchical manner, from DNA packaging to higher order genome associations such as TADs, and the significance of radial positioning of genomic loci. We will then elaborate on the dynamics of genome organization during development, and how genome architecture plays an important role in cell fate determination. Finally, we will discuss and how misregulation can be a factor in human disease.